Cupressus sempervirens extract inhibited human basal cell carcinoma tumorigenesis, local invasion, and angiogenic property. (January 2017) - Amirnia, Mehdi; Mokhtari, Fatemeh; Rezabakhsh, Aysa; Nabat, Elaheh; Khodaiani, Effat; Khalilzadeh, Sajad; Movassaghpour, Ali; Delazar, Abbas; Sadeghi, Anali; Rahbarghazi, Reza
Abstract Basal cell carcinoma, a noninvasive and rarely metastatic tumor, correlates with clinical and histological involvement of basal epithelial cells. It occurs due to dysregulation of hedgehog-patched1 signaling pathway. The current study was conducted to evaluate the in vitro cytotoxic effects ofCupressus sempervirens methanolic extract against primary basal cell carcinoma cells, over a period of 48 h. We measured protein level of Annexin-V and the leakage rate of lactate dehydrogenase in cells being exposed to 420 μM extract. In addition to transcript levels ofPTCH-1,  a receptor of  of hedgehog signaling pathway, angiogenic activity of tumor cells were determined in terms of the amount of vascular endothelial growth factor and angiopoietin-2, and metastatic levels of matrix metalloproteinase 2 and 9. The cytotoxicity test results showed that BCC cells survival decreased dose-dependently over 48 h after exposure to plant extract. The expression of Annexin-V was induced (p  < 0.05) in treated cells which coincided with raised levels of lactate dehydrogenase in supernatant media (p  < 0.05). Noticeably, the expression ofPTCH -1, vascular endothelial growth factor, angiopoietin-2, and matrix metalloproteinase 2 and 9 were robustly decreased. Interestingly, 6-month clinical trial follow-up ofC. sempervirens extract 5% ointment showed antitumor activity against cutaneous basal cell carcinoma by the reduction of tumor and inflammatory cells replaced with fibrotic stroma. The data of present experiment may suggest that the methanolic extracts ofC. sempervirens possess oncostatic and cytotoxic properties, and therefore, can be prescribed as natural protective and therapeutic ingredients for basal cell associate cutaneous tumor.